Right to a fair trial in international law - Clooney, Amal; Webb, Philippa (Philippa Mahal) (Oxford, United Kingdom ; New York, NY : Oxford University Press, 2020)
"The Right to a Fair Trial in International Law" brings together the diverse sources of international law that define the right to a fair trial in the context of criminal (as opposed to civil, administrative or other) proceedings. The book provides a comprehensive explanation of what the right to a fair trial means in practice under international law and focuses on factual scenarios that practitioners and judges in court face. Each of the book's fifteen chapters deal with one component of the right to a fair trial as defined in Article 14 of the International Covenant on Civil and Political Rights. Highlighting both consensus and divisions in the international jurisprudence in this area, this book provides a valuable resource to practitioners and scholars dealing with breaches of one of the most fundamental human rights.
Right to a competent, independent and impartial tribunal established by law -- Right to a public trial -- Right to be presumed innocent -- Right to prepare a defence -- Right to counsel -- Right to be tried without undue delay -- Right to be present -- Right to examine witnesses -- Right to an interpreter -- Right to silence -- Right to appeal -- Right to equality -- Right not to be subject to double jeopardy -- Remedies.
Includes bibliographical references and index.
Keywords: International Covenant on Civil and Political Rights -- (1966 December 16); Fair trial; International law; International courts; Due process of law